Social entrepreneurship model for Co-operative (Co-op) in Malaysia: a case of KoMajuJaya Berhad - Zainol, Fakhrul Anwar; Wan Daud, Wan Norhayate; Abdullah, Zulhamri; Yaacob, Mohd Rafi (Global Institute for Research & Education, 2014)
This case study explore how social entrepreneurship model for Co-operative can be implemented on the context of eradicating urban povertyin Malaysia. This study begins with the introduction of brief background of KoMajuJaya Berhad (KoMajuJaya). A details of KoMajuJaya’s organization structure, vision, mission and its functions are described thoroughly. The study documents the operational characteristics and environment of the social entrepreneurship of KoMajuJaya.We measure three key characters of social entrepreneurship –innovation, proactiveness, and risk taking on the current practice of organization. We found that KoMajuJaya is being proactively in achieving their mission. Specifically. KoMajuJaya can be considered as innovation, proactiveness and risk taking in being efficient financially. The organization focuses on elevating their members’ socio-economic living standard through shares and other profitable investments. This study implies that social entrepreneurship model can be effectively practiced in the co-operativesettingwhich may leverage the networks in a moderate competitive business environment.